Anode and method for producing the same
Patent Information
- Application Number
- JP2021132227
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-08-16
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2041-08-16
Abstract
Description
[Technical field]
[0001] The present invention relates to a negative electrode and a method for producing the negative electrode. [Background technology]
[0002] In recent years, small electronic devices such as mobile terminals have become widespread, and there is a strong demand for further miniaturization, weight reduction, and longer life. In response to such market demands, development of secondary batteries that are small, lightweight, and capable of obtaining high energy density has been promoted. The application of these secondary batteries is being considered not only for small electronic devices, but also for large electronic devices such as automobiles and power storage systems such as homes.
[0003] Among these, lithium-ion secondary batteries are attracting great attention because they can be easily made small and have a high capacity, and because they can provide a higher energy density than lead batteries or nickel-cadmium batteries.
[0004] The lithium ion secondary battery includes a positive electrode, a negative electrode, a separator, and an electrolyte solution, and the negative electrode contains a negative electrode active material involved in charge and discharge reactions.
[0005] While carbon-based active materials are widely used as negative electrode active materials, recent market demands have called for further improvements in battery capacity. To improve battery capacity, the use of silicon as a negative electrode active material is being considered. This is because the theoretical capacity of silicon (4199mAh / g) is more than 10 times greater than the theoretical capacity of graphite (372mAh / g), and a significant improvement in battery capacity can be expected. In the development of silicon materials as negative electrode active materials, not only silicon itself but also compounds such as alloys and oxides are being considered. In addition, the active material shape is being considered, ranging from the standard coating type for carbon-based active materials to an integrated type that is directly deposited on the current collector.
[0006] However, when silicon is used as the main raw material for the negative electrode active material, the negative electrode active material expands and contracts during charging and discharging, making it prone to cracking, mainly near the surface layer of the negative electrode active material. In addition, ionic substances are generated inside the active material, making the negative electrode active material prone to cracking. When the surface layer of the negative electrode active material cracks, a new surface is created, increasing the reaction area of the active material. At this time, a decomposition reaction of the electrolyte occurs on the new surface, and a coating, which is a decomposition product of the electrolyte, is formed on the new surface, consuming the electrolyte. This makes the cycle characteristics more likely to deteriorate.
[0007] To date, various studies have been conducted on negative electrode materials and electrode configurations for lithium-ion secondary batteries that use silicon materials as the main component in order to improve the initial battery efficiency and cycle characteristics.
[0008] Specifically, in order to obtain good cycle characteristics and high safety, silicon and amorphous silicon dioxide are simultaneously deposited using a gas phase method (see, for example, Patent Document 1). Also, in order to obtain high battery capacity and safety, a carbon material (electron conductive material) is provided on the surface layer of silicon oxide particles (see, for example, Patent Document 2). Furthermore, in order to improve cycle characteristics and obtain high input / output characteristics, an active material containing silicon and oxygen is prepared, and an active material layer with a high oxygen ratio is formed near the current collector (see, for example, Patent Document 3). Also, in order to improve cycle characteristics, oxygen is contained in the silicon active material, and the active material is formed so that the average oxygen content is 40 at% or less and the oxygen content is high in the area close to the current collector (see, for example, Patent Document 4).
[0009] In addition, in order to improve the initial charge-discharge efficiency, a nano-composite containing Si phase, SiO2, and MyO metal oxide is used (see, for example, Patent Document 5). Also, for improving cycle characteristics, SiOx (0.8 ≦ x ≦ 1.5, particle size range = 1 μm to 50 μm) and a carbon material are mixed and fired at high temperature (see, for example, Patent Document 6). Further, for improving cycle characteristics, the molar ratio of oxygen to silicon in the negative electrode active material is set to 0.1 to 1.2, and the active material is controlled within a range where the difference between the maximum value and the minimum value of the molar ratio near the interface between the active material and the current collector is 0.4 or less (see, for example, Patent Document 7). In addition, in order to improve the battery load characteristics, a metal oxide containing lithium is used (see, for example, Patent Document 8). Also, in order to improve cycle characteristics, a hydrophobic layer such as a silane compound is formed on the surface layer of the silicon material (see, for example, Patent Document 9). Further, for improving cycle characteristics, silicon oxide is used, and conductivity is imparted by forming a graphite film on its surface layer (see, for example, Patent Document 10). In Patent Document 10, regarding the shift value obtained from the RAMAN spectrum of the graphite film, a broad peak appears at 1330 cm -1 and 1580 cm -1 and the intensity ratio I 1330 / I 1580 is such that 1.5 < I 1330 / I 1580 < 3. Also, for improving high battery capacity and cycle characteristics, particles having a silicon microcrystalline phase dispersed in silicon dioxide are used (see, for example, Patent Document 11). Further, in order to improve overcharge and overdischarge characteristics, a silicon oxide in which the atomic ratio of silicon to oxygen is controlled to 1:y (0 < y < 2) is used (see, for example, Patent Document 12).
[0010] The lithium ion secondary battery using silicon oxide was shipped by Hitachi Maxell in June 2010 for a rectangular secondary battery for smartphones that adopted a nano-silicon composite (see, for example, Non-Patent Document 1). The silicon oxide proposed by Hohl is Si 0+ ~Si 4+It is a composite material with various oxidation states (see Non-Patent Document 2). Kapaklis has also proposed a disproportionated structure in which silicon oxide is separated into Si and SiO2 by applying a thermal load to the silicon oxide (see Non-Patent Document 3). Miyachi et al. have focused on Si and SiO2, which contribute to charging and discharging, among silicon oxides with disproportionated structures (see Non-Patent Document 4), and Yamada et al. have proposed the following reaction formula between silicon oxide and Li (see Non-Patent Document 5).
[0011] 2SiO(Si+SiO2) + 6.85Li + + 6.85e - → 1.4Li 3.75 Si + 0.4Li4SiO4 + 0.2SiO2
[0012] The above reaction formula shows that Si and SiO2 that make up silicon oxide react with Li, and are separated into Li silicide, Li silicate, and some unreacted SiO2.
[0013] The Li silicate formed here is irreversible, and once formed, it is considered to be a stable substance that does not release Li. The capacity per mass calculated from this reaction formula is close to the experimental value, and is recognized as the reaction mechanism of silicon oxide. Kim et al. have defined the irreversible component associated with the charge and discharge of silicon oxide, Li silicate, as Li4SiO4, and 7 Li-MAS-NMR and 29 The identification was carried out using Si-MAS-NMR (see Non-Patent Document 6).
[0014] This irreversible capacity is the weakest point of silicon oxide, and there is a need to improve it. Kim et al. have used a Li pre-doping method to form Li silicate in advance, which has significantly improved the initial efficiency of the battery and produced a negative electrode that can withstand practical use (see Non-Patent Document 7).
[0015] Also, instead of doping the electrode with Li, a method of treating the powder has been proposed, which has achieved an improvement in irreversible capacity (see Patent Document 13). [Prior art documents] [Patent documents]
[0016] [Patent Document 1] JP 2001-185127 A [Patent Document 2] JP 2002-042806 A [Patent Document 3] JP 2006-164954 A [Patent Document 4] JP 2006-114454 A [Patent Document 5] JP 2009-070825 A [Patent Document 6] JP 2008-282819 A [Patent Document 7] JP 2008-251369 A [Patent Document 8] JP 2008-177346 A [Patent Document 9] JP 2007-234255 A [Patent Document 10] JP 2009-212074 A [Patent Document 11] JP 2009-205950 A [Patent Document 12] Japanese Patent Application Publication No. 06-325765 [Patent Document 13] JP 2015-156355 A [Non-patent literature]
[0017] [Non-Patent Document 1] Battery Association of Japan's journal "Denchi", May 1, 2010 issue, page 10 [Non-Patent Document 2] A. Hohl, T. Wieder, P. A. van Aken, T. E. Weirich, G. Denninger, M. Vidal, S. Oswald, C. Deneke, J. Mayer, and H. Fuess: J. Non-Cryst. Solids, 320, (2003), 255. [Non-Patent Document 3] V. Kapaklis, J. Non-Crystalline Solids, 354 (2008) 612 [Non-Patent Document 4] Mariko Miyachi, Hironori Yamamoto, and Hidemasa Kawai, J. Electrochem. Soc. 2007 volume 154, issue 4, A376-A380 [Non-Patent Document 5] M. Yamada, M. Inaba, A. Ueda, K. Matsumoto, T. Iwasaki, T. Ohzuku, J.Electrochem. Soc., 159, A1630 (2012) [Non-Patent Document 6] Taeahn Kim, Sangjin Park, and Seung M. Oh, J. Electrochem. Soc. volume 154, (2007), A1112-A1117. [Non-Patent Document 7] Hye Jin Kim, Sunghun Choi, Seung Jong Lee, Myung Won Seo, Jae Goo Lee, Erhan Deniz, Yong Ju Lee, Eun Kyung Kim, and Jang Wook Choi,. Nano Lett. 2016, 16, 282-288. [Non-Patent Document 8] Supervised by Noboru Sato, "The Forefront of Development of In-Vehicle Lithium-Ion Batteries", CMC Publishing, November 27, 2020, pp. 96-111 [Summary of the Invention] [Problem to be solved by the invention]
[0018] As mentioned above, in recent years, small electronic devices such as mobile terminals have been improved in performance and functionality, and lithium-ion secondary batteries, which are the main power sources for these devices, are required to have increased battery capacity. As one method for solving this problem, the development of a lithium-ion secondary battery consisting of a negative electrode mainly made of silicon material is desired. In addition, lithium-ion secondary batteries using silicon materials are desired to have initial charge / discharge characteristics and cycle characteristics that are similar to those of lithium-ion secondary batteries using carbon-based active materials. Therefore, by using silicon oxide modified by insertion and partial desorption of Li as the negative electrode active material, cycle characteristics and initial charge / discharge characteristics have been improved. Recently, silicon oxide is mainly used, Li is contained in advance, and Li silicate is generated, reducing the irreversible capacity, which is a disadvantage of silicon oxide, and it has actually begun to be put on the market. Even if a battery is prototyped by replacing 100% of Li-SiO-C (Non-Patent Document 8), which uses Li in this silicon oxide, with carbon negative electrode material, the capacity of this battery is only increased by the latter half of the 20% range compared to a battery using a carbon negative electrode material. This means that when considering the increasing performance of small electronic devices (5G, etc.) and the increased driving range of electric vehicles, further improvements in battery capacity will be required.
[0019] The present invention has been made in consideration of the above problems, and has an object to provide a negative electrode that can significantly increase the capacity while maintaining excellent battery characteristics, and a method for producing such a negative electrode. [Means for solving the problem]
[0020] In order to solve the above problems, the present invention provides a negative electrode current collector having a roughened surface, a negative electrode active material layer provided on the negative electrode current collector; A negative electrode having the negative electrode active material layer includes negative electrode active material particles having a compound of lithium, silicon, and oxygen, and a ratio O / Si of the oxygen to the silicon constituting the negative electrode active material particles is in the range of 0.8 to 1.2, The negative electrode active material layer has a multilayer structure consisting of two or more layers, and each layer of the multilayer structure of the negative electrode active material layer has a layer containing a tetravalent silicon compound containing at least one of lithium and oxygen in an upper portion.
[0021] The negative electrode of the present invention has a negative electrode active material layer containing negative electrode active material particles having a compound of lithium, silicon, and oxygen, and therefore can improve the battery capacity. In addition, the negative electrode of the present invention can directly support the negative electrode active material layer on the roughened surface of the negative electrode current collector without using a binder, a conductive assistant, etc., and can reduce the area of the electrode that is not involved in charging and discharging, and can also reduce excess voids, thereby significantly improving the energy density of the electrode.
[0022] Furthermore, the negative electrode of the present invention can maintain excellent battery characteristics since the ratio O / Si of oxygen to silicon constituting the negative electrode active material particles is in the range of 0.8 to 1.2.
[0023] In addition, the negative electrode active material layer having a multilayer structure consisting of two or more layers can realize smooth insertion of Li while suppressing decomposition of the electrolyte. Furthermore, each layer of the multilayer structure of the negative electrode active material layer has a layer containing a tetravalent silicon compound containing at least one of lithium and oxygen in the upper part, and this layer can act as a relaxation layer. Since the non-aqueous electrolyte can enter this part, Li doping (Li insertion) is possible in each layer, ion concentration is suppressed, and expansion occurs uniformly. Li desorption is also possible in each layer, so contraction also occurs uniformly. As a result, the expansion and contraction of the negative electrode due to charging and discharging is mitigated, and a stable negative electrode active material layer can be maintained.
[0024] In other words, the negative electrode of the present invention can significantly increase the capacity while maintaining excellent battery characteristics, particularly excellent cycle characteristics.
[0025] The tetravalent silicon compound preferably contains one or more compounds selected from SiO2 and Li4SiO4.
[0026] SiO2 reduces the expansion and contraction of the negative electrode, and Li4SiO4 allows charging and discharging to proceed more smoothly, so the presence of SiO2 and Li4SiO4 can further improve the battery characteristics.
[0027] The negative electrode active material layer is The negative electrode active material particles; a composite compound filled between the particles and on the surface of the negative electrode active material particles, in which at least carbon atoms and oxygen atoms are chemically bonded and which does not form an alloy with the negative electrode active material particles; It is preferable that the composition has the following formula:
[0028] This composite compound can act as a protective layer to protect the interface between the negative electrode active material layer and the electrolyte solution. Due to the presence of such a composite compound, the negative electrode of the present invention can exhibit better cycle characteristics.
[0029] In this case, the complex compound may be a ring-opening decomposition product of a complex between an ether solvent and a polyphenylene compound or a polycyclic aromatic compound, or a ring-opening decomposition product of the complex formed with lithium.
[0030] Such a composite compound can be easily formed during the process of doping negative electrode active material particles with Li, depending on the method used.
[0031] After at least 20 charge / discharge cycles, the negative electrode active material particles are 1+ ~Si 3+ It is preferable that the silicon compound state is the one having the largest amount of the silicon compound.
[0032] Such a negative electrode allows for smoother charging and discharging.
[0033] When the negative electrode active material particles are defined as primary particles, the negative electrode active material layer forms secondary particles, which are aggregates of the primary particles, after charging and discharging, and it is preferable that the secondary particles have a morphology in which they are separated from each other in the in-plane direction.
[0034] Such a negative electrode can more effectively prevent the electrode from collapsing due to charging and discharging, and can maintain a stable negative electrode active material layer.
[0035] The negative electrode active material particles preferably have a peak attributable to a Si(111) crystal plane obtained by X-ray diffraction using Cu-Kα radiation before charge / discharge, and the crystallite size corresponding to the crystal plane is preferably 1.0 nm or less.
[0036] Such a negative electrode can suppress reactivity with the electrolyte, and can further improve the battery characteristics.
[0037] The negative electrode current collector preferably has a ten-point average roughness Rz of its surface of 1.5 μm or more and 5.0 μm or less.
[0038] A negative electrode including such a negative electrode current collector can not only stably support the negative electrode active material layer, but also make it possible to make the density of the negative electrode active material particles in the negative electrode active material layer appropriate, and as a result, can exhibit better battery characteristics.
[0039] The present invention also provides a method for producing a negative electrode of the present invention, comprising the steps of: A step of winding the negative electrode current collector around a can roll having a curvature; a step of vapor-depositing a film containing silicon and / or silicon monoxide having a multilayer structure consisting of two or more layers on the negative electrode current collector while running the negative electrode current collector on the can roll; A step of blowing an oxygen-containing gas onto the silicon and / or silicon monoxide-containing film to form a multi-layer structure containing silicon dioxide on the top of each layer; doping the layer of the multilayer structure with lithium to form the negative electrode active material layer; The present invention provides a method for producing a negative electrode, comprising the steps of:
[0040] According to such a method for producing a negative electrode of the present invention, it is possible to produce a negative electrode of the present invention that can significantly increase the capacity while maintaining the battery characteristics.
[0041] In the step of forming layers of the multilayer structure, layers of the multilayer structure are formed, each layer of which contains a silicon oxide including the silicon dioxide; In the step of forming the negative electrode active material layer, it is preferable that the multilayered layer is immersed in a solution containing lithium to modify the silicon oxide by an oxidation-reduction method to form a compound having lithium, silicon, and oxygen, and form a composite compound that is filled between and on the surface layers of the negative electrode active material particles, in which at least carbon atoms and oxygen atoms are chemically bonded to each other and that does not alloy with the negative electrode active material particles.
[0042] By forming such a composite compound, a negative electrode that can exhibit better cycle characteristics can be manufactured. Effect of the Invention
[0043] As described above, when the negative electrode of the present invention is used as the negative electrode of a secondary battery, the capacity can be significantly increased while maintaining excellent battery characteristics. For example, when the negative electrode of the present invention is used as the negative electrode of a secondary battery, it is possible to obtain high initial efficiency, high capacity, high input characteristics, and high cycle characteristics.
[0044] Furthermore, the method for producing the negative electrode of the present invention can produce a negative electrode of the present invention that can significantly increase the capacity while maintaining excellent battery characteristics. For example, the method for producing the negative electrode of the present invention can produce a negative electrode that has a high capacity and good initial charge / discharge characteristics when used as a negative electrode for a secondary battery while obtaining good cycle characteristics. [Brief description of the drawings]
[0045] [Figure 1] FIG. 1 is a schematic cross-sectional view showing an example of the configuration of a negative electrode of the present invention. [Diagram 2] 1 is a cross-sectional SEM image of an example of a negative electrode of the present invention. [Diagram 3] 4 is a cross-sectional SEM image of another example of the negative electrode of the present invention. [Figure 4] FIG. 1 is an exploded view showing a configuration example (laminate film type) of a lithium ion secondary battery including a negative electrode of the present invention. [Diagram 5] 1 is a part of an XPS spectrum of a surface layer of a negative electrode active material of Example 2. [Figure 6] 13 is another part of the XPS spectrum of the negative electrode active material surface layer of Example 2. [Figure 7] 4 is a SEM image of the surface of the negative electrode active material layer of Example 2 after charging and discharging. [Figure 8] 1 is a part of an XPS spectrum of a negative electrode active material layer of Example 2 after 20 charge / discharge cycles. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0046] As mentioned above, one method to increase the battery capacity of lithium-ion secondary batteries is to use a negative electrode that uses silicon oxide as the main material. Lithium-ion secondary batteries using silicon oxide are expected to have initial charge / discharge characteristics that are close to those of lithium-ion secondary batteries using carbon-based active materials. In addition, a significant increase in capacity can be expected by using Li-doped SiO, which can improve the initial charge / discharge characteristics, but further improvement in capacity is required when considering vehicle applications.
[0047] Therefore, the inventors have conducted extensive research in order to obtain a negative electrode that, when used as a negative electrode for a secondary battery, can obtain high cycle characteristics while improving initial charge / discharge characteristics and increasing battery capacity, and have arrived at the present invention.
[0048] That is, the present invention provides a negative electrode current collector having a roughened surface, a negative electrode active material layer provided on the negative electrode current collector; A negative electrode having the negative electrode active material layer includes negative electrode active material particles having a compound of lithium, silicon, and oxygen, and a ratio O / Si of the oxygen to the silicon constituting the negative electrode active material particles is in the range of 0.8 to 1.2, The negative electrode active material layer has a multilayer structure consisting of two or more layers, and each layer of the multilayer structure of the negative electrode active material layer has a layer containing a tetravalent silicon compound containing at least one of lithium and oxygen in an upper portion.
[0049] The present invention also provides a method for producing the negative electrode of the present invention, comprising the steps of: A step of winding the negative electrode current collector around a can roll having a curvature; a step of vapor-depositing a film containing silicon and / or silicon monoxide having a multilayer structure consisting of two or more layers on the negative electrode current collector while running the negative electrode current collector on the can roll; A step of blowing an oxygen-containing gas onto the silicon and / or silicon monoxide-containing film to form a multi-layer structure containing silicon dioxide on the top of each layer; doping the layer of the multilayer structure with lithium to form the negative electrode active material layer; The method for producing a negative electrode comprises the steps of:
[0050] The present invention will be described in detail below, but the present invention is not limited thereto.
[0051] <Negative electrode> First, the configuration of the negative electrode of the present invention will be described with reference to the drawings.
[0052] Fig. 1 shows a schematic cross-sectional view of an example of the negative electrode of the present invention. As shown in Fig. 1, the negative electrode 10 has a configuration including a negative electrode current collector 11 and a negative electrode active material layer 12 provided on a surface 11a of the negative electrode current collector 11. The negative electrode active material-containing layer 12 may be provided on both surfaces 11a of the negative electrode current collector 11 as shown in Fig. 1, or may be provided on only one surface 11a.
[0053] The surface 11a of the negative electrode current collector 11 is a roughened surface. That is, the negative electrode active material layer 12 is provided on the roughened surface 11a of the negative electrode current collector 11.
[0054] The negative electrode current collector 11 and the negative electrode active material layer 12 will be described below.
[0055] [Negative electrode current collector] The negative electrode current collector 11 is made of a material having excellent electrical conductivity and excellent mechanical strength. Examples of the conductive material that can be used for the negative electrode current collector 11 include copper (Cu) and nickel (Ni). It is preferable that this conductive material is a material that does not form an intermetallic compound with lithium (Li).
[0056] The negative electrode current collector 11 preferably contains carbon (C) and / or sulfur (S) in addition to the main elements. This is because the physical strength of the negative electrode current collector is improved. In particular, when the current collector has an active material layer that expands during charging, if the current collector contains the above elements, this has the effect of suppressing deformation of the electrode including the current collector. The contents of the above contained elements are not particularly limited, but are preferably 100 mass ppm or less for each. This is because a higher deformation suppression effect can be obtained. Such a deformation suppression effect can further improve cycle characteristics.
[0057] Moreover, the surface 11a of the negative electrode current collector 11 must be roughened, and preferably the ten-point average roughness Rz of the surface is 1.5 μm or more and 5.0 μm or less. If the negative electrode 10 includes the negative electrode current collector 11 having the surface 11a with such a desirable average roughness Rz, not only can the negative electrode active material layer 12 be supported more stably, but also the density of the negative electrode active material particles in the negative electrode active material layer 12 can be made appropriate, and as a result, better battery characteristics can be exhibited. The roughened negative electrode current collector 11 is, for example, a metal foil that has been electrolytically treated, embossed, or chemically etched.
[0058] [Negative electrode active material layer] The negative electrode active material layer 12 of the negative electrode 10 of the present invention has negative electrode active material particles having a compound of lithium, silicon, and oxygen, i.e., silicon compound particles containing lithium and oxygen, and is provided on the negative electrode current collector 11. It can be said that the negative electrode 10 has a structure in which the negative electrode active material particles are directly supported on the roughened surface 11a of the negative electrode current collector 11.
[0059] The negative electrode 10 of the present invention contains negative electrode active material particles, which are silicon compound particles, and therefore can improve the battery capacity. In addition, unlike a general electrode, the negative electrode 10 of the present invention can directly support the negative electrode active material layer 12 on the roughened surface 11a of the negative electrode current collector 11 without using a binder, a conductive assistant, or the like, and can reduce the area of the electrode that is not involved in charging and discharging, and can also reduce excess voids, thereby significantly improving the energy density of the electrode.
[0060] In this way, by using a negative electrode 10 having a densely supported negative electrode active material layer 12, it is possible to increase the energy density of the battery in a way that is not possible with, for example, a powder electrode.
[0061] Furthermore, the negative electrode 10 of the present invention has a ratio O / Si of oxygen to silicon constituting the negative electrode active material particles in the range of 0.8 to 1.2. If the ratio O / Si is 0.8 or more, the oxygen ratio is higher than that of silicon alone, and therefore the cycle characteristics are good. If the ratio O / Si is 1.2 or less, the resistance of the silicon oxide does not become too high, which is preferable. Among these, it is preferable that the composition of SiOx has x close to 1. This is because high cycle characteristics can be obtained. Note that the composition of the silicon compound in the present invention does not necessarily mean 100% purity, and may contain a trace amount of impurity elements.
[0062] On the other hand, if the ratio O / Si is less than 0.8, the capacity is increased, but the Si 0+ The area of reaction between the O and the electrolyte increases, and the cycle characteristics deteriorate. In addition, if the O / Si ratio exceeds 1.2, the O / Si becomes a load substance, which also deteriorates the battery characteristics. The O / Si ratio is a molar ratio, and it is desirable to keep it as close to 1 as possible.
[0063] In order to introduce Li more smoothly, it is preferable to form the negative electrode active material layer 12 into a multi-layer structure consisting of two or more layers at the timing of forming the negative electrode active material layer 12. This is because a negative electrode active material layer having a multi-layer structure consisting of two or more layers can realize smooth insertion of Li while suppressing decomposition of the electrolyte. However, this leads to an increase in the reaction area, and if left as is, the battery characteristics will be insufficient.
[0064] Therefore, in the negative electrode 10 of the present invention, each layer of the multilayer structure of the negative electrode active material layer 12 has, in the upper part, a layer containing a tetravalent silicon compound containing at least one of lithium and oxygen.
[0065] This layer acts as a buffer layer, and not only functions to introduce and remove Li, but also to buffer expansion and contraction during charging and discharging, thereby maintaining the battery characteristics.
[0066] More specifically, since the non-aqueous electrolyte can penetrate into this relaxation layer, Li doping (Li insertion) is possible in each layer, ion concentration is suppressed, and expansion occurs uniformly. Li desorption is also possible in each layer, so contraction also occurs uniformly. As a result, the expansion and contraction of the negative electrode due to charging and discharging is mitigated, and a stable negative electrode active material layer can be maintained.
[0067] In other words, the negative electrode 10 of the present invention can significantly increase the capacity while maintaining excellent battery characteristics, particularly excellent cycle characteristics.
[0068] The tetravalent silicon compound preferably contains one or more selected from SiO2 and Li4SiO4, because SiO2 further reduces the expansion and contraction of the negative electrode, and Li4SiO4 allows charging and discharging to proceed more smoothly.
[0069] Furthermore, the negative electrode active material particles having a compound of lithium, silicon, and oxygen can be adjacent to each other in the formed negative electrode active material layer 12. It is preferable that the spaces between the particles and the surface layer of the negative electrode active material particles are filled with a composite compound (also called a "C, O compound") in which at least carbon atoms and oxygen atoms are chemically bonded and which does not alloy with the negative electrode active material particles, i.e., does not react with the negative electrode active material particles.
[0070] This composite compound plays a role as a protective layer that protects the interface between the negative electrode active material layer and the electrolyte. By filling the spaces between and on the surface of the negative electrode active material particles with the above composite compound that acts as a protective layer that suppresses reaction with the electrolyte, it is possible to propose a negative electrode active material layer 12 that suppresses decomposition of the electrolyte, facilitates the introduction of Li, and maintains the battery characteristics. The presence of such a composite compound makes it possible to exhibit better cycle characteristics.
[0071] Furthermore, the primary particles of the negative electrode active material particles have a multi-layer structure, and the interlayer portions are also filled with the above-mentioned composite compound, thereby ensuring reactivity with the electrolyte.
[0072] The complex compound that functions as the protective layer may be a ring-opening decomposition product of a complex of an ether-based solvent with a polyphenylene compound or a polycyclic aromatic compound, or a ring-opening decomposition product of the complex formed with lithium.
[0073] Such a composite compound can be easily formed in the process of doping negative electrode active material particles with Li using an oxidation-reduction method.
[0074] In particular, it is preferable that the composite compound in which at least carbon and oxygen atoms are chemically bonded and which can act as a protective layer contains lithium in part. That is, it is preferable that the composite compound contains lithium in at least part. By compounding a composite oxide containing carbon and oxygen with lithium and containing lithium in part, the composite oxide exhibits behavior similar to a kind of solid electrolyte, and in particular, it is easier for Li to permeate than when only carbon and oxygen are contained, and it is possible to improve the diffusibility of Li, so that the battery characteristics can be further improved.
[0075] In addition, silicon monoxide, which is a typical example of a common silicon oxide, is often expressed as a compound of Si with 0 to 4 valences. For example, when the Si2p spectrum of silicon monoxide is obtained by photoelectron spectroscopy, Si 0+ The peak appears near the binding energy of 99 eV, and the Si 4+ The peaks of the valence 0 and Si 4+ On the other hand, when the negative electrode active material particles containing silicon are directly supported on the negative electrode current collector 11, the structure of the silicon compound can be changed by controlling the state of the roughened part of the surface 11a of the negative electrode current collector 11, the temperature of the negative electrode current collector 11 (the substrate on which the deposition is performed), the running speed of the negative electrode current collector 11, the gas ejection, and the like.
[0076] In addition, the negative electrode active material particles are repeatedly charged and discharged, for example, after at least 20 charge / discharge cycles. 0+ Silicon in the state of Si 1+ ~Si 3+ and silicon in the compound state of Si 1+ ~Si 3+ It is more desirable that the compound state be the most prevalent.
[0077] S 0+ When silicon in this state becomes the main component, the reaction with the electrolyte is promoted. 1+ ~Si 3+ It forms a complex with silicon oxide in the valence state (compound state) of Si 0+The structure prevents the silicon in this state from coming into direct contact with the electrolyte, allowing for smooth discharge.
[0078] The valence state of silicon in the negative electrode active material particles can be determined by subjecting the photoelectron spectrum obtained by the above-mentioned photoelectron spectroscopy to waveform separation processing and confirming the presence or absence of peaks attributable to each valence state of silicon in the spectrum.
[0079] The state of the valence of silicon in the negative electrode active material layer and the negative electrode active material particles contained therein can be confirmed, for example, by using a scanning X-ray photoelectron spectrometer PHI Quantera II manufactured by ULVAC-PHI, Inc. At this time, the X-ray beam diameter can be set to 100 μm, and a neutralization gun can be used.
[0080] The negative electrode active material particles grow in a vapor phase due to the roughened portion of the surface 11a of the negative electrode current collector 11. When these are defined as primary particles, it is preferable that they form secondary particles, which are aggregates of the primary particles, after charging and discharging.
[0081] This can be controlled by changing the roughening state of the surface 11a of the negative electrode current collector 11. For example, if the roughening interval is wide, the secondary particle group becomes small. On the other hand, if the roughening interval is narrow and the primary particles are too densely packed, it becomes difficult for secondary particles to be generated during charging and discharging.
[0082] It is desirable that these secondary particles are separated from each other in the in-plane direction. By performing charge and discharge in this state, a stable negative electrode active material layer 12 can be maintained.
[0083] The negative electrode active material layer before charging and discharging is composed of Si 0+It is desirable that the negative electrode active material particles are as non-crystalline (amorphous) as possible. Specifically, the crystallite size of Si(111) is desirably 1.0 nm or less. Therefore, it is desirable that the negative electrode active material particles have a peak due to the Si(111) crystal plane obtained by X-ray diffraction using Cu-Kα radiation before charging and discharging, and the crystallite size corresponding to this crystal plane is 1.0 nm or less. If the negative electrode active material particles contain such particles, the reactivity with the electrolyte can be suppressed, and the battery characteristics can be further improved.
[0084] The degree of Li silicate enlargement and the degree of Si crystallization (for example, the crystallite size corresponding to the Si(111) crystal plane) can be confirmed by XRD (X-ray Diffraction). XRD measurement can be performed, for example, under the following conditions. XRD: Bruker D8 ADVANCE As the X-ray diffraction device, for example, D8 ADVANCE manufactured by Bruker can be used. The X-ray source is Cu Kα radiation, and a Ni filter is used, and measurements are performed from 10 to 40° with an output of 40 kV / 40 mA, a slit width of 0.3°, a step width of 0.008°, and a counting time of 0.15 seconds per step.
[0085] Next, specific examples of the negative electrode of the present invention will be described in more detail with reference to FIG. 2 and FIG.
[0086] Fig. 2 and Fig. 3 are cross-sectional SEM images of an example of the negative electrode of the present invention. The member with protrusions on the surface shown in the lower region of Fig. 2 and Fig. 3 is a negative electrode current collector with a roughened surface. The ten-point mean roughness Rz of the surface of the negative electrode current collector shown in Fig. 3 is larger than the ten-point mean roughness Rz of the surface of the negative electrode current collector shown in Fig. 2.
[0087] In Fig. 2 and Fig. 3, the part that grows in a fan shape around the protuberance of the roughened surface of the negative electrode current collector is the negative electrode active material particle. The negative electrode active material particle constitutes a negative electrode active material layer having a multilayer structure. In the example shown in Fig. 2, the thickness of each layer of the negative electrode active material layer is about 400 nm. Note that the negative electrode shown in Fig. 3 has a larger number of layers of the negative electrode active material layer than the negative electrode shown in Fig. 2.
[0088] Black streaks can be seen at the top of each layer of the negative electrode active material in the SEM images of Figures 2 and 3. These are layers that contain a compound of tetravalent silicon that contains at least one of lithium and oxygen. In these areas, decomposition products of the solvent are generated by doping with Li, but there are fine voids.
[0089] Although it is difficult to clearly see in the SEM images of Figures 2 and 3, a composite compound in which at least carbon atoms and oxygen atoms are chemically bonded is filled between the particles and in the surface layer of the negative electrode active material particles. Thus, in the negative electrode shown in cross section in Figures 2 and 3, a negative electrode active material layer having the above-mentioned negative electrode active material particles and the above-mentioned composite compound is provided on the negative electrode current collector.
[0090] As is clear from the SEM images of Figs. 2 and 3, the negative electrode active material layer of the negative electrode of the present invention has very few voids and contains densely packed negative electrode active material particles.
[0091] [Method of manufacturing the negative electrode] The method for producing a negative electrode of the present invention is characterized by comprising the steps of: winding the negative electrode current collector around a can roll having a curvature; vapor-depositing a film containing silicon and / or silicon monoxide having a multilayer structure consisting of two or more layers on the negative electrode current collector while running the negative electrode current collector on the can roll; spraying an oxygen-containing gas onto the film containing silicon and / or silicon monoxide to form a multilayer structure layer containing silicon dioxide on the upper part of each layer; and doping the layer of the multilayer structure with lithium to form the negative electrode active material layer.
[0092] The negative electrode of the present invention can be manufactured by any method for manufacturing the negative electrode of the present invention, however, the method for manufacturing the negative electrode of the present invention is not limited to the manufacturing method of the present invention described here.
[0093] Hereinafter, an example of the method for producing the negative electrode of the present invention will be specifically described, but the method for producing the negative electrode of the present invention is not limited to the example described below.
[0094] First, a film containing silicon and / or silicon monoxide having a multilayer structure consisting of two or more layers is produced. Here, a film containing silicon and / or silicon monoxide having a multilayer structure is vapor-phase grown on a negative electrode current collector. The film containing silicon can contain silicon particles. The film containing silicon monoxide can contain silicon monoxide particles, which are silicon compound (silicon oxide) particles containing oxygen. Therefore, the film containing silicon and / or silicon monoxide having a multilayer structure consisting of two or more layers can contain silicon-containing particles.
[0095] This multilayered film containing silicon and / or silicon monoxide can be formed by depositing, for example, a silicon vapor flow or silicon oxide gas on a negative electrode current collector having a roughened surface, for example, a roughened foil (for example, a roughened copper foil) having a surface ten-point average roughness Rz of 1.5 μm to 5.0 μm (for example, 2.5 μm). In the method for producing a negative electrode of the present invention, the negative electrode current collector is wound around a can roll having a curvature. The curvature (R) of the can roll is, for example, 4 m. -1 More than 20m -1 It is preferable that:
[0096] A specific example of a method for forming a multi-layered film containing silicon and / or silicon monoxide is as follows.
[0097] A silicon monoxide film can be formed, for example, by the following procedure. First, a raw material that generates silicon oxide gas is heated at a temperature of 1100°C or higher under reduced pressure to generate silicon oxide gas. At this time, a mixture of metal silicon powder and silicon dioxide powder can be used as the raw material. Considering the presence of oxygen on the surface of the metal silicon powder and trace amounts of oxygen in the reactor, it is desirable for the mixture molar ratio to be in the range of 0.9<metal silicon powder / silicon dioxide powder<1.2.
[0098] It is possible to introduce reducing gas (hydrogen) into silicon dioxide gas, but it is difficult to introduce sufficient hydrogen into steam that moves at close to the speed of sound.
[0099] As a result, it is preferable to form the silicon monoxide film using silicon metal and silicon dioxide powder as raw materials.
[0100] The silicon oxide gas generated as described above is deposited on the roughened portion of the surface of the negative electrode current collector, and becomes primary particles having a columnar structure.
[0101] Also, a silicon film can be formed by vapor deposition using, for example, metallic silicon.
[0102] When forming the silicon film and / or silicon monoxide film, the structure of the primary particles can also be changed by changing the roughened structure of the surface of the negative electrode current collector.
[0103] The heat of solidification during deposition and the radiant heat from the heating unit promote crystallization of the negative electrode active material layer.
[0104] Therefore, in the method for producing the negative electrode of the present invention, the film is formed while the negative electrode current collector is running on a can roll having a curvature. This allows vapor growth to be performed without crystallizing Si while reducing the thermal load.
[0105] In particular, silicon oxide, unlike silicon, is sublimable, allowing for rapid deposition, and there is no need to worry about radiant heat from molten silicon, which is an issue with silicon films. Therefore, silicon oxide is suitable for forming active materials by vapor deposition.
[0106] In the method for producing a negative electrode of the present invention, multilayer film formation (for example, reciprocating multilayer film formation) is performed while the negative electrode current collector is running on a can roll having a curve, so that part of the surface of each layer is deposited at an angle, causing voids.
[0107] Deposition can also be performed on both roughened surfaces of the negative electrode current collector, for example, deposition can be performed on one roughened surface of the negative electrode current collector, then the negative electrode current collector can be turned over and deposition can be performed on the other roughened surface of the negative electrode current collector.
[0108] A gas containing oxygen is sprayed onto the film containing silicon and / or silicon monoxide thus formed, to form a multi-layer structure containing silicon dioxide on the top of each layer.
[0109] The oxygen-containing gas is not particularly limited as long as it contains oxygen, but may be, for example, nitrogen gas containing oxygen.
[0110] By blowing the oxygen-containing gas, oxygen can enter the voids in the upper part of each layer, and oxygen can be introduced into each layer. This also allows at least a part of the silicon and / or silicon monoxide to be converted to silicon dioxide in the upper part of each layer. In other words, by blowing the oxygen-containing gas, a multi-layer structure can be formed in which each layer contains silicon oxide including silicon dioxide.
[0111] Next, Li is doped (inserted) into the multilayer structure containing silicon dioxide on the top of each layer prepared as described above. This results in an anode active material layer containing anode active material particles containing silicon oxide particles into which lithium is inserted. That is, this modifies the silicon oxide particles, and a Li compound is generated inside the silicon oxide particles. The insertion of Li is preferably performed by an oxidation-reduction method.
[0112] In the modification by the oxidation-reduction method, for example, lithium can be inserted by first immersing the negative electrode active material layer containing silicon oxide particles in solution A in which lithium is dissolved in an ether solvent. This solution A may further contain a polycyclic aromatic compound or a linear polyphenylene compound. After lithium insertion, active lithium can be desorbed from the silicon oxide particles by immersing the silicon active material particles in solution B containing a polycyclic aromatic compound or its derivative. The solvent for this solution B can be, for example, an ether-based solvent, a ketone-based solvent, an ester-based solvent, an alcohol-based solvent, an amine-based solvent, or a mixed solvent thereof. Alternatively, after immersion in solution A, the obtained silicon active material particles may be heat-treated under an inert gas. The Li compound can be stabilized by heat treatment. After that, washing may be performed using a method such as washing with alcohol, alkaline water in which lithium carbonate is dissolved, weak acid, or pure water.
[0113] As the ether solvent used in solution A, diethyl ether, tert-butyl methyl ether, tetrahydrofuran, dioxane, 1,2-dimethoxyethane, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, or a mixture thereof can be used. Among these, it is particularly preferable to use tetrahydrofuran, dioxane, or 1,2-dimethoxyethane. These solvents are preferably dehydrated and deoxygenated.
[0114] Furthermore, the polycyclic aromatic compound contained in solution A may be one or more of naphthalene, anthracene, phenanthrene, naphthacene, pentacene, pyrene, picene, triphenylene, coronene, chrysene, and derivatives thereof, and the linear polyphenylene compound may be one or more of biphenyl, terphenyl, and derivatives thereof.
[0115] The polycyclic aromatic compound contained in solution B may be one or more of naphthalene, anthracene, phenanthrene, naphthacene, pentacene, pyrene, picene, triphenylene, coronene, chrysene, and derivatives thereof.
[0116] As the ether solvent for solution B, diethyl ether, tert-butyl methyl ether, tetrahydrofuran, dioxane, 1,2-dimethoxyethane, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, and the like can be used.
[0117] As the ketone solvent, acetone, acetophenone, etc. can be used.
[0118] As the ester solvent, methyl formate, methyl acetate, ethyl acetate, propyl acetate, isopropyl acetate, and the like can be used.
[0119] As the alcohol-based solvent, methanol, ethanol, propanol, isopropyl alcohol, and the like can be used.
[0120] As the amine solvent, methylamine, ethylamine, ethylenediamine, and the like can be used.
[0121] When Li-doping is performed in the voids generated by multilayer film formation using a curved can roll, decomposition products of the solvent are generated, but minute voids remain.
[0122] In this manner, a negative electrode can be obtained that includes a negative electrode current collector and a multilayered negative electrode active material layer provided on the negative electrode current collector, in which each layer of the multilayered structure has a layer on the upper portion that contains a tetravalent silicon compound containing at least one of lithium and oxygen.
[0123] The ratio O / Si of oxygen to silicon constituting the negative electrode active material contained in the negative electrode active material layer can be adjusted, for example, by the film formation rate during multilayer film formation and the amount of oxygen blown after film formation.
[0124] In the manner described above, the negative electrode of the present invention can be produced.
[0125] Furthermore, a composite compound in which at least carbon atoms and oxygen atoms are chemically bonded and which can be filled between and on the surface layers of the negative electrode active material particles can be formed, for example, by ring-opening decomposition or the like of a composite of the ether-based solvent and the polyphenylene compound or the polycyclic aromatic compound contained in solution A, or by ring-opening decomposition or the like of a composite in which the composite forms a complex with lithium (for example, a composite of an ether-based solvent and a polycyclic aromatic compound complexed with Li).
[0126] At this time, it is possible to control the state of the filled coating (composite compound) by adjusting the temperature of the solvent, the type and concentration of the polyphenylene compound or polycyclic aromatic compound contained in the solvent, and the concentration of the polycyclic aromatic compound complexed with Li.
[0127] The resulting complex compound may contain multiple types of compounds.
[0128] That is, in the step of forming the negative electrode active material layer, a layer having a multilayer structure obtained by spraying an oxygen-containing gas is immersed in a solution containing lithium to modify the silicon oxide by an oxidation-reduction method to form a compound having lithium, silicon, and oxygen, and also to form a composite compound which is filled between and on the surface of the negative electrode active material particles in the negative electrode active material layer, in which at least carbon atoms and oxygen atoms are chemically bonded, and which does not alloy with the negative electrode active material particles.
[0129] <Lithium-ion secondary battery> The negative electrode of the present invention can be used in the negative electrode of a non-aqueous electrolyte secondary battery, for example, a lithium ion secondary battery.
[0130] Next, as a specific example of a nonaqueous electrolyte secondary battery in which the negative electrode of the present invention can be used, an example of a laminate film type lithium ion secondary battery will be described.
[0131] [Configuration of laminated film type secondary battery] The laminate film type lithium ion secondary battery 30 shown in FIG. 4 is a battery in which a wound electrode body 31 is housed inside a sheet-like exterior member 35. This wound electrode body 31 has a separator between the positive electrode and the negative electrode and is wound. There are also cases where the electrode body is not wound, but a laminate having a separator between the positive electrode and the negative electrode is housed. In either electrode body, a positive electrode lead 32 is attached to the positive electrode, and a negative electrode lead 33 is attached to the negative electrode. The outermost periphery of the electrode body is protected by a protective tape.
[0132] The positive electrode lead 32 and the negative electrode lead 33 are led out in one direction, for example, from the inside to the outside of the exterior member 35. The positive electrode lead 32 is formed of a conductive material such as aluminum, and the negative electrode lead 33 is formed of a conductive material such as nickel or copper.
[0133] The exterior member 35 is, for example, a laminate film in which a fusion layer, a metal layer, and a surface protection layer are laminated in this order, and the outer peripheral edges of the fusion layers of the two films of this laminate film are fused together or pasted together with an adhesive so that the fusion layer faces the electrode body 31. The fusion part is, for example, a film such as polyethylene or polypropylene, and the metal part is aluminum foil, etc. The protection layer is, for example, nylon, etc.
[0134] To prevent outside air from entering, an adhesive film 34 is inserted between the exterior member 35 and each of the positive electrode lead 32 and the negative electrode lead 33. The material for this is, for example, polyethylene, polypropylene, or polyolefin resin.
[0135] Each component will be described below.
[0136] [Positive electrode] The positive electrode has a positive electrode active material layer on either or both sides of a positive electrode current collector, similar to the negative electrode 10 in FIG.
[0137] The positive electrode current collector is made of a conductive material such as aluminum.
[0138] The positive electrode active material layer contains one or more types of positive electrode materials (positive electrode active materials) capable of absorbing and releasing lithium ions, and may contain other materials such as a positive electrode binder, a positive electrode conductive assistant, and a dispersant depending on the design.
[0139] The positive electrode material is preferably a lithium-containing compound. Examples of the lithium-containing compound include a composite oxide made of lithium and a transition metal element, or a phosphate compound containing lithium and a transition metal element. Among these positive electrode materials, compounds containing at least one of nickel, iron, manganese, and cobalt are preferred. Examples of the chemical formula of these compounds include Li x M1O2 or Li y It is represented by M2PO4. In the formula, M1 and M2 represent at least one transition metal element. The values of x and y vary depending on the charge / discharge state of the battery, but are generally expressed as 0.05≦x≦1.10 and 0.05≦y≦1.10.
[0140] Examples of composite oxides containing lithium and transition metal elements include lithium cobalt composite oxide (Li x CoO2), lithium nickel composite oxide (Li x Examples of the lithium nickel cobalt composite oxide include lithium nickel cobalt aluminum composite oxide (NCA) and lithium nickel cobalt manganese composite oxide (NCM).
[0141] Examples of the phosphate compound containing lithium and a transition metal element include a lithium iron phosphate compound (LiFePO4) and a lithium iron manganese phosphate compound (LiFe 1-u Mn uExamples include PO4 (0 < u < 1)). By using these cathode materials, high battery capacity can be obtained, and excellent cycle characteristics can also be obtained.
[0142] As the cathode binder, for example, any one or more of polymer materials, synthetic rubbers, etc. can be used. Examples of the polymer material include polyvinylidene fluoride, polyimide, polyamideimide, aramid, polyacrylic acid, lithium polyacrylate, sodium polyacrylate, carboxymethyl cellulose, etc. Examples of the synthetic rubber include styrene-butadiene rubber, fluorine rubber, ethylene propylene diene, etc.
[0143] As the cathode conductive assistant, for example, any one or more of carbon materials such as carbon black, acetylene black, graphite, ketjen black, carbon nanotubes, carbon nanofibers, etc. can be used.
[0144] [Negative electrode] As the negative electrode of the secondary battery, the negative electrode of the present invention is used. It is preferable that the negative electrode charge capacity of the negative electrode constituting this secondary battery is larger than the electric capacity (charge capacity as a battery) obtained from the positive electrode active material agent. Thereby, precipitation of lithium metal on the negative electrode can be suppressed.
[0145] In this example, the positive electrode active material layer is provided on a part of both sides of the positive electrode current collector, and similarly, the negative electrode active material layer of the present invention is also provided on a part of both sides of the negative electrode current collector. In this case, for example, it is preferable that the negative electrode active material layer provided on the negative electrode current collector is provided with a region where there is no opposing positive electrode active material layer. This is for performing a stable battery design.
[0146] In the region where the above-mentioned negative electrode active material layer and positive electrode active material layer do not face each other, it is hardly affected by charge and discharge. Therefore, the state of the negative electrode active material layer is maintained as it is immediately after formation, and thereby the composition of the negative electrode active material, etc. can be accurately investigated with good reproducibility without depending on the presence or absence of charge and discharge.
[0147] [Separator] The separator separates the lithium metal or the positive electrode from the negative electrode, and allows lithium ions to pass through while preventing current short circuit caused by contact between the two electrodes. The separator is formed of a porous film made of, for example, synthetic resin or ceramic, and may have a laminated structure in which two or more types of porous films are laminated. Examples of synthetic resins include polytetrafluoroethylene, polypropylene, and polyethylene.
[0148] [Electrolyte] At least a portion of each of the positive electrode active material layer and the negative electrode active material layer, or the separator, is impregnated with a liquid nonaqueous electrolyte (electrolytic solution). This electrolytic solution contains an electrolyte salt dissolved in a solvent, and may contain other materials such as additives.
[0149] The solvent may be, for example, a non-aqueous solvent. Examples of non-aqueous solvents include ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, 1,2-dimethoxyethane, and tetrahydrofuran. Among these, it is desirable to use at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate. This is because better characteristics can be obtained. In this case, more advantageous characteristics can be obtained by combining a high-viscosity solvent such as ethylene carbonate or propylene carbonate with a low-viscosity solvent such as dimethyl carbonate, ethyl methyl carbonate, or diethyl carbonate. This is because the dissociation and ion mobility of the electrolyte salt are improved.
[0150] In particular, it is desirable that the solvent contains at least one of halogenated chain carbonates or halogenated cyclic carbonates. This allows a stable coating to be formed on the surface of the negative electrode active material during charging and discharging, particularly during charging. Here, the halogenated chain carbonate is a chain carbonate having a halogen as a constituent element (at least one hydrogen is substituted with a halogen). In addition, the halogenated cyclic carbonate is a cyclic carbonate having a halogen as a constituent element (i.e., at least one hydrogen is substituted with a halogen).
[0151] The type of halogen is not particularly limited, but fluorine is preferred because it forms a better coating than other halogens. Also, the more halogens there are, the more desirable they are because the resulting coating is more stable and the decomposition reaction of the electrolyte is reduced.
[0152] Examples of halogenated chain carbonates include fluoromethyl methyl carbonate, difluoromethyl methyl carbonate, etc. Examples of halogenated cyclic carbonates include 4-fluoro-1,3-dioxolan-2-one, 4,5-difluoro-1,3-dioxolan-2-one, etc.
[0153] It is preferable that the solvent additive contains an unsaturated carbon-bonded cyclic carbonate. This is because a stable coating is formed on the negative electrode surface during charging and discharging, and the decomposition reaction of the electrolyte can be suppressed. Examples of the unsaturated carbon-bonded cyclic carbonate include vinylene carbonate and vinylethylene carbonate.
[0154] It is also preferable that the solvent additive contains sultone (cyclic sulfonic acid ester), because this improves the chemical stability of the battery. Examples of sultones include propane sultone and propene sultone.
[0155] Furthermore, it is preferable that the solvent contains an acid anhydride, because this improves the chemical stability of the electrolyte. As the acid anhydride, for example, propane disulfonic acid anhydride can be mentioned.
[0156] The electrolyte salt may include at least one of light metal salts such as lithium salts, for example. Examples of the lithium salt include lithium hexafluorophosphate (LiPF6) and lithium tetrafluoroborate (LiBF4).
[0157] The content of the electrolyte salt is preferably 0.5 mol / kg or more and 2.5 mol / kg or less relative to the solvent, because high ionic conductivity can be obtained.
[0158] [Manufacturing method of laminate film type secondary battery] The laminate film type secondary battery described above can be manufactured, for example, by the following procedure.
[0159] First, a positive electrode is prepared using the above-mentioned positive electrode material. First, a positive electrode active material is mixed with a positive electrode binder, a positive electrode conductive assistant, etc., if necessary, to prepare a positive electrode mixture, which is then dispersed in an organic solvent to prepare a positive electrode mixture slurry. Next, the mixture slurry is applied to a positive electrode current collector using a coating device such as a knife roll or a die coater having a die head, and the mixture is dried with hot air to obtain a positive electrode active material layer. Finally, the positive electrode active material layer is compression molded using a roll press machine or the like. At this time, heating may be performed, and compression may be repeated multiple times.
[0160] Next, following the same procedure as in the production of the negative electrode 10 described above, a negative electrode active material layer is formed on the negative electrode current collector to produce the negative electrode.
[0161] When preparing the positive and negative electrodes, active material layers are formed on both sides of the positive and negative current collectors, respectively. At this time, the lengths of the active material applied on both sides of each electrode may be offset (see FIG. 1).
[0162] Next, the electrolyte is adjusted. Next, the positive electrode lead 32 is attached to the positive electrode current collector by ultrasonic welding or the like, and the negative electrode lead 33 is attached to the negative electrode current collector. Next, the positive electrode and the negative electrode are laminated with a separator interposed therebetween, and then wound to prepare the wound electrode body 31, and a protective tape is attached to the outermost periphery. Next, the wound electrode body 31 is molded to have a flat shape. Next, the wound electrode body 31 is sandwiched between folded film-like exterior members 35, and then the insulating parts of the exterior members are bonded to each other by a heat fusion method, and the wound electrode body 31 is sealed in a state in which only one direction is open. Next, an adhesive film 34 is inserted between the positive electrode lead 32 and the negative electrode lead 33 and the exterior member 35. Next, a predetermined amount of the above-prepared electrolyte is poured from the open part, and vacuum impregnation is performed. After the impregnation, the open part is bonded by a vacuum heat fusion method. In this manner, the laminate film type secondary battery 30 can be manufactured.
[0163] In the non-aqueous electrolyte secondary battery such as the laminate film type secondary battery 30 produced above, the negative electrode utilization rate during charging and discharging is preferably 93% or more and 99% or less. If the negative electrode utilization rate is in the range of 93% or more, the initial charge efficiency does not decrease and the battery capacity can be greatly improved. In addition, if the negative electrode utilization rate is in the range of 99% or less, Li does not precipitate and safety can be ensured. EXAMPLES
[0164] The present invention will be specifically described below using examples and comparative examples, but the present invention is not limited to these.
[0165] Comparative Example 1 In order to use the capacity when a graphite negative electrode is used as a standard, a graphite negative electrode was prototyped.
[0166] The negative electrode of Comparative Example 1 was formed by mixing artificial graphite: conductive assistant (acetylene black): SBR (styrene-butadiene rubber): CMC (carboxymethyl cellulose) in a ratio of 95.7% by mass:1% by mass:1.8% by mass:1.5% by mass.
[0167] Comparative Example 2 An electrode was fabricated using powdered Li-doped SiO with a carbon coating (denoted as "Li-SiO-C").
[0168] The electrode of Comparative Example 2 was prepared by mixing Li-SiO-C:PAA-Na (sodium polyacrylate):conductive assistant (acetylene black) in a ratio of 90% by mass:8% by mass:2% by mass.
[0169] Li-Si-O was prepared by the following procedure. First, silicon and silicon dioxide were mixed as raw materials, vaporized at 1300℃, and then deposited on a deposition substrate and quenched to produce SiO blocks. The SiO blocks were crushed to a median diameter of 7μm, and then doped with Li using an oxidation-reduction method. After doping, samples were prepared by heat treatment to stabilize the Li silicate.
[0170] (Comparative Examples 3 to 7 and Examples 1 to 4) In Comparative Examples 3 to 7 and Examples 1 to 4, negative electrodes were produced by the following procedure: In these examples, a surface-roughened copper foil having a ten-point average roughness (roughness) Rz of 2.5 μm was used as the negative electrode current collector.
[0171] [Preparation of negative electrode precursor] (Example 1 and Comparative Example 5) In Example 1 and Comparative Example 5, granular silicon metal was placed in a carbon crucible, and the silicon was melted and vaporized under vacuum using an electron gun. -1 A surface-roughened copper foil (which will serve as the negative electrode current collector) was wrapped around a can roll, and the surface-roughened copper foil was run back and forth over the can roll to form a five-layer silicon film on the surface-roughened copper foil.
[0172] In Example 1 and Comparative Example 5, after forming a silicon film with a five-layer structure, nitrogen gas containing oxygen was sprayed onto the silicon film, thereby forming a multilayer structure containing silicon dioxide on the top of each layer.
[0173] In Example 1 and Comparative Example 5, the film formation rate and the amount of oxygen blown after film formation were adjusted so that the ratio O / Si of silicon to oxygen constituting the final negative electrode active material particles would be the values shown in the table below. In this manner, the negative electrode precursors of Example 1 and Comparative Example 5 were prepared.
[0174] Comparative Example 3 In Comparative Example 3, a silicon film having a five-layer structure was formed in the same manner as in Example 1, but the subsequent blowing of oxygen-containing nitrogen gas was not performed. In this manner, the negative electrode precursor of Comparative Example 3 was produced.
[0175] Comparative Example 4 In Comparative Example 4, metal silicon and silicon dioxide were placed in a carbon crucible and heated for 10 -2 The vapor was taken out by heating at 1200° C. in an atmosphere of a vacuum degree of 100 Pa. The vapor was directly supported on the roughened copper foil as in Comparative Example 3.
[0176] In this manner, a negative electrode was obtained having a roughened copper foil and a negative electrode active material layer containing silicon oxide provided on the roughened copper foil.
[0177] (Examples 2 and 3, and Comparative Example 6) In Examples 2 and 3 and Comparative Example 6, a raw material containing a mixture of silicon metal and silicon dioxide was introduced into a furnace in the same manner as in Comparative Example 4, and the mixture was heated for 10 -2 The gas was evaporated in a vacuum of 10 Pa. A movable device was used, and the curvature R was 10 m. -1 A surface-roughened copper foil (which will serve as the negative electrode current collector) was wrapped around a can roll, and the surface-roughened copper foil was run back and forth over the can roll to form a five-layer silicon monoxide film on the surface-roughened copper foil.
[0178] In Examples 2 and 3 and Comparative Example 6, after forming a silicon monoxide film with a five-layer structure, nitrogen gas containing oxygen was sprayed onto the silicon monoxide, thereby forming a multilayer structure containing silicon dioxide on the top of each layer.
[0179] In Example 3 and Comparative Example 6, the film formation rate was adjusted and hydrogen or oxygen was blown into the steam as necessary to form a film so that the ratio O / Si of silicon to oxygen constituting the finally obtained negative electrode active material particles would be the values shown in the table below. In Examples 2 and 3 and Comparative Example 6, the amount of oxygen blown after film formation was adjusted so that the ratio O / Si of silicon to oxygen constituting the finally obtained negative electrode active material particles would be the values shown in the table below. In this manner, the negative electrode precursors of Examples 2 and 3 and Comparative Example 6 were prepared.
[0180] (Example 4 and Comparative Example 7) In Example 4, the negative electrode precursor of Example 4 was produced in the same manner as in Example 2, except that 20 multilayer films were formed by controlling the film formation rate. In Comparative Example 7, the negative electrode precursor of Comparative Example 7 was produced in the same manner as in Example 2, except that one single layer film was formed without running the roughened copper foil.
[0181] [Lithium insertion and filling layer formation] (Examples 1 to 4, and Comparative Examples 3 and 5 to 7) The negative electrode precursors obtained in Examples 1 to 4 and Comparative Examples 3 and 5 to 7 were sufficiently cooled and then taken out, and lithium was inserted into the silicon compound by an oxidation-reduction method using an ether solvent with the moisture content reduced to 50 mass ppm, thereby obtaining the negative electrodes of Examples 1 to 4 and Comparative Examples 3 and 5 to 7, each of which includes a negative electrode active material layer after lithium insertion.
[0182] The negative electrode active material layers after lithium insertion obtained in Examples 1 to 4 and Comparative Examples 3, 5 to 7 were observed with a scanning electron microscope (SEM), and it was confirmed that the interlayers of the negative electrode active material layers in Examples 1 to 4 and Comparative Examples 3, 5 and 6 were dark. The presence of a dark portion was also confirmed in the upper part of the single-layered negative electrode active material layer in Comparative Example 7. It can be seen that the dark portion is a portion that is easily charged, and that the layer is one in which silicon is oxidized and has a large amount of tetravalent state. In addition, the negative electrode active material layers after lithium insertion obtained in Comparative Example 7, Examples 1 to 4, and Comparative Examples 3 and 5 to 7 were analyzed by X-ray photoelectron spectroscopy (XPS) to confirm the presence of a filling layer containing a composite compound in which carbon atoms and oxygen atoms are chemically bonded, and to examine the valence state of silicon on the surface of the negative electrode active material particles and the ratio O / Si of silicon to oxygen constituting the negative electrode active material particles.
[0183] As a result, it was found that the negative electrode active material layers after lithium insertion obtained in Examples 1 to 4 and Comparative Examples 3 and 5 to 7 had negative electrode active material particles having a compound of lithium, silicon, and oxygen, and a filling layer containing a complex compound in which carbon atoms and oxygen atoms are chemically bonded, which was filled between the particles and on the surface layer of the negative electrode active material.
[0184] Furthermore, the results of the XPS analysis confirmed that in the negative electrodes of Examples 1 to 4, the composite compound in which carbon atoms and oxygen atoms are chemically bonded to each other contained lithium in part.
[0185] In addition, from the XPS spectra of Example 2 shown in Figures 5 and 6, more specifically, from the peak near 55 eV in the XPS spectrum of Li1s (Figure 5) and the peak near 101 eV in the XPS spectrum of Si2p (Figure 6), it can be seen that a layer containing a tetravalent Si compound containing lithium and oxygen exists in the surface layer portion (upper part) of each layer of the negative electrode active material layer of Example 2. From this, it was confirmed that SiO2 and Li4SiO4 exist. It was also confirmed that a layer containing a tetravalent Si compound containing lithium and oxygen exists in the upper part of each layer of the negative electrode active material layer of Examples 1 and 3.
[0186] The negative electrodes of Comparative Examples 3 to 7 were subjected to SEM observation and XPS analysis in the same manner as in Example 1. These results are summarized in Table 1 below.
[0187] Example 5 In Example 5, a Li insertion electrode was obtained in the same manner as in Example 2, and then washed with ether containing 10% water to remove the surface filling layer. In this way, a negative electrode of Example 5 was obtained.
[0188] (Examples 6 to 8) In Examples 6 to 8, each negative electrode was prepared in the same manner as in Example 2, except that the film formation was performed by adjusting the film formation distance, film formation rate, copper foil running speed, and opening with which the deposition flow contacted, so that the crystallite size due to the Si(111) crystal plane contained in the negative electrode active material particles became the value shown in Table 2 below.
[0189] (Examples 9 to 14) In Examples 9 to 14, negative electrodes were produced in the same manner as in Example 2, except that the roughness Rz of the surface-roughened copper foil was changed between 0.5 μm and 7 μm as shown in Table 2 below.
[0190] The negative electrodes of Examples 5 to 14 were subjected to SEM observation and XPS analysis in the same manner as in Example 2. The results are summarized in Table 2 below.
[0191] As a result, it was found that the negative electrode active material layer after lithium insertion obtained in Examples 5 to 14 has a negative electrode active material particle having a compound of lithium, silicon, and oxygen, and a filling layer containing a composite compound in which carbon atoms and oxygen atoms are chemically bonded, which is filled between the particles of the negative electrode active material and on the surface layer, and the ratio O / Si of silicon and oxygen constituting the negative electrode active material particle is 0.8 or more and 1.2 or less. In addition, it was confirmed that the negative electrode active material layer of the negative electrode of Examples 5 to 14 has a five-layer structure like Example 2, and that a layer containing a tetravalent Si compound containing lithium and oxygen exists on the upper part of each layer.
[0192] Furthermore, the results of the XPS analysis confirmed that in the negative electrodes of Examples 6 to 14, the composite compounds in which carbon atoms and oxygen atoms are chemically bonded to each other contained lithium in part.
[0193] [Assembling a coin battery for testing] Next, ethylene carbonate (EC) and dimethyl carbonate (DMC) were mixed to prepare a non-aqueous solvent, and then an electrolyte salt (lithium hexafluorophosphate: LiPF6) was dissolved in the non-aqueous solvent to prepare an electrolyte solution (non-aqueous electrolyte). In this case, the composition of the solvent was EC:DMC=30:70 in volume ratio, and the content of the electrolyte salt was 1 mol / kg relative to the solvent. 2.0 mass% of fluoroethylene carbonate (FEC) was added as an additive.
[0194] Next, a coin cell for the initial efficiency test was assembled as follows: First, a 1 mm thick Li foil was punched out to a diameter of 16 mm and attached to an aluminum clad.
[0195] Next, the negative electrode obtained above was punched out to a diameter of 15 mm, and this was placed opposite a Li foil attached to an aluminum clad via a separator. After injection of an electrolyte, a 2032 coin battery was produced.
[0196] [Measurement of initial efficiency] The initial efficiency was measured under the following conditions. First, the coin battery for the initial efficiency test was charged (initial charge) in CCCV mode with a charge rate equivalent to 0.03C. CV was 0V and the end current was 0.04mA. Next, CC discharge (initial discharge) was performed with a discharge rate of 0.03C and an end voltage of discharge of 1.2V.
[0197] When investigating the initial charge / discharge characteristics, the initial efficiency (hereinafter sometimes referred to as initial efficiency) was calculated using the formula: initial efficiency (%) = (initial discharge capacity / initial charge capacity) x 100.
[0198] [Production and evaluation of lithium secondary batteries] From the initial data obtained, the counter positive electrode was designed so that the utilization rate of the negative electrode would be 95%. The utilization rate was calculated from the capacity of the positive and negative electrodes obtained with the counter electrode Li according to the following formula. Utilization rate = (positive electrode capacity - negative electrode loss) / (negative electrode capacity - negative electrode loss) x 100 Based on this design, lithium secondary batteries of the examples and comparative examples were manufactured. Battery evaluation was performed on each of the lithium secondary batteries of the examples and comparative examples.
[0199] The cycle characteristics were investigated as follows. First, in order to stabilize the battery, two cycles of charge and discharge were performed at 0.2C in an atmosphere of 25°C, and the discharge capacity of the second cycle was measured. The battery cycle characteristics were calculated from the discharge capacity of the third cycle, and the battery test was stopped after 100 cycles. Charge and discharge were performed at 0.7C and 0.5C. The charge voltage was 4.3V, the discharge end voltage was 2.5V, and the charge end rate was 0.07C.
[0200] The discharge capacity at the second cycle measured in the cycle characteristic test was regarded as the capacity achieved by each negative electrode.
[0201] The cycle characteristics (capacity maintenance rate up to 100 cycles), initial efficiency, and capacity increase rate based on Comparative Example 1 for each of the negative electrodes of the Examples and Comparative Examples are summarized in Tables 1 and 2 below.
[0202] [SEM observation of the negative electrode active material layer surface after charging and discharging] The negative electrode active material layer of the negative electrode of Example 2 after charging and discharging was observed using a scanning electron microscope (SEM). Fig. 7 shows an SEM image of the negative electrode active material layer of the negative electrode of Example 2 after charging and discharging (post-discharge state).
[0203] As shown in Fig. 7, in the negative electrode active material layer of the negative electrode of Example 2 in a discharged state, small particles, i.e., primary particles, are aggregated to form secondary particles. The secondary particles are separated from each other in the in-plane direction. The part visible between the secondary particles is a part of the surface of the negative electrode current collector.
[0204] When the negative electrode active material layers of the negative electrodes of Examples 1 and 3 to 14 after charging and discharging were observed by SEM, SEM images similar to those in FIG. 7 were obtained.
[0205] [XPS spectrum after 20 charge / discharge cycles] The negative electrode of Example 2 was subjected to XPS analysis after 20 charge / discharge cycles, and a portion of the obtained XPS spectrum is shown in FIG.
[0206] As shown in FIG. 8, the XPS spectrum of the negative electrode active material layer of the negative electrode of Example 2 after 20 charge / discharge cycles shows a peak at about 99 eV that is attributed to silicon in a zero-valence state, and a peak at about 101.9 eV that is attributed to silicon in a zero-valence state. 1+ ~Si 3+ and a broad peak assigned to silicon in the compound state.
[0207] [XRD analysis of negative electrode active material particles] The negative electrode active material particles contained in the negative electrode active material layer of each negative electrode were analyzed by XRD. The crystallite size corresponding to the Si(111) crystal plane contained in the negative electrode active material particles was calculated based on the Scherrer formula from the peak due to the Si(111) crystal plane. The results are summarized in Tables 1 and 2 below. Note that the negative electrode active material particles of Examples 1 to 5, 9 to 14 and Comparative Examples 3 to 7 had amorphous Si.
[0208] [Table 1]
[0209] [Table 2]
[0210] [result] In the above Tables 1 and 2, the rate of increase in discharge capacity per volume (Wh / L) relative to Comparative Example 1 is shown as the capacity increase rate.
[0211] As is clear from Tables 1 and 2, the negative electrodes of Examples 1 to 14 were able to significantly increase the capacity compared to the graphite negative electrode of Comparative Example 1 while maintaining the battery characteristics (cycle characteristics and initial efficiency).
[0212] On the other hand, the negative electrode of Comparative Example 2, which was prepared using powdered Li-doped SiO, had a lower capacity than the negative electrodes of Examples 1 to 14. This is believed to be because the negative electrode of Comparative Example 2 was prepared using powder instead of deposition, and therefore contained a binder that is not involved in charge and discharge, and further had many excess voids.
[0213] In addition, the negative electrode of Comparative Example 3 had significantly inferior cycle characteristics compared to Examples 1 to 14. In Comparative Example 3, the silicon film of the five-layer structure was not sprayed with a gas containing oxygen. Therefore, each layer of the negative electrode active material layer of the negative electrode of Comparative Example 3 did not have a layer containing a tetravalent silicon compound containing at least one of lithium and oxygen in the upper part. Therefore, in the negative electrode of Comparative Example 3, ion concentration occurred in a part of the negative electrode active material layer during charging and discharging, and the negative electrode deteriorated due to the expansion and contraction of the negative electrode caused by charging and discharging.
[0214] The capacity increase rate per volume in Comparative Example 4 was lower than in Examples 1 to 14. This is believed to be because Li was not inserted into the silicon oxide in Comparative Example 4.
[0215] Comparative Examples 5 and 6 and Examples 1 to 3 are examples in which the amount of oxygen in the bulk (oxygen ratio O / Si) was adjusted.
[0216] Silicon oxide is produced from silicon and silicon dioxide, so it is difficult to increase or decrease the amount of oxygen. In addition, the valence of silicon oxide with an O / Si ratio of 0.7 (Comparative Example 5) could not be controlled, and a significant amount of silicon element remained.
[0217] To achieve even lower oxygen levels, it is necessary not only to introduce hydrogen into the steam for active reduction, but also to significantly reduce the deposition rate.
[0218] In the negative electrode of Comparative Example 5, the oxygen ratio O / Si was set to 0.7, and as a result, the cycle characteristics were lower than those of the negative electrodes of Examples 1 to 3. This is believed to be because, in the negative electrode of Comparative Example 5, the oxygen ratio O / Si was set to 0.7, so that the area where zero-valent Si reacts with the electrolyte became too large.
[0219] On the other hand, when the amount of oxygen was increased, the deposition rate was also decreased and oxygen was blown directly into the vapor flow, but as the amount of oxygen increased, it became difficult to prepare a silicon oxide film.
[0220] In the negative electrode of Comparative Example 6, the oxygen ratio O / Si was set to 1.3, and as a result, the initial efficiency was lower than that of the negative electrodes of Examples 1 to 3. This is considered to be because the oxygen ratio O / Si was set to 1.3 in the negative electrode of Comparative Example 6, which resulted in an excessive amount of the load substance.
[0221] The cycle characteristics of the negative electrode of Comparative Example 7 were significantly decreased. This is believed to be because the silicon oxide film was formed to form a single layer film without running the roughened copper foil, making it impossible to alleviate the expansion and contraction of the negative electrode.
[0222] Examples 6 to 9 are examples in which the influence of silicon crystallization on battery characteristics was examined.
[0223] The negative electrodes of Examples 6 to 9 were able to increase the capacity more than the negative electrode of Comparative Example 1 while maintaining the battery characteristics better than Comparative Examples 2 to 7.
[0224] On the other hand, Example 2, in which the silicon was amorphous, was able to exhibit superior battery characteristics to the negative electrodes of Examples 6 to 9, in which the silicon was highly crystallized.
[0225] Examples 9 to 14 shown in Table 2 are examples aimed at finding the most suitable point by adjusting the surface roughness Rz of the roughened copper foil used as a negative electrode current collector.
[0226] From the results of Example 2 and Examples 9 to 14, it can be seen that the negative electrodes of Examples 2 and 10 to 13, in which the surface roughness Rz of the roughened copper foil is 1.5 μm or more and 5.0 μm or more, exhibited better cycle characteristics than the negative electrode of Example 9, in which the roughness Rz is less than 1.5 μm, and Example 14, in which the roughness Rz exceeded 5.0 μm. This is believed to be because the negative electrodes of Examples 1 and 10 to 13, in which the surface roughness Rz of the roughened copper foil is 1.5 μm or more and 5.0 μm or more, are able to adequately hold the negative electrode active material layer by the roughened portion on the surface of the current collector, and are able to more adequately suppress peeling of the active material during charging and discharging.
[0227] The present invention is not limited to the above-described embodiment. The above-described embodiment is merely an example, and anything that has substantially the same configuration as the technical idea described in the claims of the present invention and exhibits similar effects is included in the technical scope of the present invention. [Explanation of symbols]
[0228] REFERENCE SIGNS LIST 10... negative electrode, 11... negative electrode current collector, 11a... surface of negative electrode current collector, 12... negative electrode active material layer, 30... lithium secondary battery (laminate film type), 31... electrode body, 32... positive electrode lead, 33... negative electrode lead, 34... adhesive film, 35... exterior member.
Claims
1. a negative electrode current collector having a roughened surface; a negative electrode active material layer provided on the negative electrode current collector; A negative electrode having the negative electrode active material layer includes negative electrode active material particles having a compound of lithium, silicon, and oxygen, and a ratio O / Si of the oxygen to the silicon constituting the negative electrode active material particles is in the range of 0.8 to 1.2, The negative electrode active material layer has a multilayer structure consisting of two or more layers, and each layer of the multilayer structure of the negative electrode active material layer has a layer containing a tetravalent silicon compound containing at least one of lithium and oxygen in an upper portion.
2. The tetravalent silicon compound is SiO 2 and Li 4 SiO 4 2. The negative electrode according to claim 1, comprising one or more selected from the group consisting of:
3. The negative electrode active material layer is The negative electrode active material particles; a composite compound filled between the particles and on the surface of the negative electrode active material particles, in which at least carbon atoms and oxygen atoms are chemically bonded and which does not form an alloy with the negative electrode active material particles; The negative electrode according to claim 1 or 2, characterized in that it has
4. 4. The negative electrode according to claim 3, wherein the composite compound is a ring-opening decomposition product of a composite of an ether-based solvent and a polyphenylene compound or a polycyclic aromatic compound, or a ring-opening decomposition product of a composite in which the composite forms a complex with lithium.
5. After at least 20 charge / discharge cycles, the negative electrode active material particles are 1+ ~Si 3+ 5. The negative electrode according to claim 1, wherein the silicon compound state is the most abundant state.
6. 6. The negative electrode according to claim 1, wherein, when the negative electrode active material particles are defined as primary particles, the negative electrode active material layer forms secondary particles which are aggregates of the primary particles after charging and discharging, and the secondary particles have a form separated from each other in an in-plane direction.
7. The negative electrode according to any one of claims 1 to 6, characterized in that the negative electrode active material particles have a peak due to a Si(111) crystal plane obtained by X-ray diffraction using Cu-Kα radiation before charge and discharge, and a crystallite size corresponding to the crystal plane is 1.0 nm or less.
8. The negative electrode according to any one of claims 1 to 7, wherein the negative electrode current collector has a surface with a ten-point average roughness Rz of 1.5 µm to 5.0 µm.
9. A method for producing a negative electrode according to any one of claims 1 to 8, comprising the steps of: A step of winding the negative electrode current collector around a can roll having a curvature; a step of vapor-depositing a film containing silicon and / or silicon monoxide having a multilayer structure consisting of two or more layers on the negative electrode current collector while running the negative electrode current collector on the can roll; A step of blowing an oxygen-containing gas onto the silicon and / or silicon monoxide-containing film to form a multi-layer structure containing silicon dioxide on the top of each layer; doping the layer of the multilayer structure with lithium to form the negative electrode active material layer; A method for producing a negative electrode, comprising:
10. In the step of forming layers of the multilayer structure, layers of the multilayer structure are formed, each layer of which contains a silicon oxide including the silicon dioxide; 10. The method for producing a negative electrode according to claim 9, wherein in the step of forming the negative electrode active material layer, the layer of the multilayer structure is immersed in a solution containing lithium to modify the silicon oxide by an oxidation-reduction method to form the compound having lithium, silicon, and oxygen, and to form a composite compound which is filled between particles and on surfaces of the negative electrode active material particles, in which at least carbon atoms and oxygen atoms are chemically bonded to each other and which is not alloyed with the negative electrode active material particles.